The Analysis of Legislative Criminal Policy of Iran, Iraq, and United Arab Emirates in Soil Conservation (Comparative Study) - ruhollah akrami; ali nabi (پژوهشهای حقوقی)
Nowadays, environmental protection and consequently soil conservation have been considered in the criminal policy of different legal systems. To recognizing the criminal policy of three Iran, Iraq, and United Arab Emirates Countries in soil conservation in the form of a case study and analytical-descriptive method, the current study tried to investigate the Positive Law to identify the political criminal reaction of these three countries in confrontation with harmful behaviors to soil. First, damages to the soil and then Positive Law and the taken criminal policy in each field have been investigated to clarify government’s approaches to the environment in general and to the soil in particular, considering that the center of attention of criminal policy is environmental protection as a fundamental value or it is dependent on human and his interest. Recognizing these components substantively and the responsibility of the criminal policy of these three countries to the criminal phenomenon (including crime and deviation) in terms of form specify their criminal policy position in the categorization of big criminal policy systems; finally, this study showed that human-oriented approach to environment has overcome ecological protection balance and considering cognitive model, the criminal policy of all three countries is near to liberal government-society in the field of soil conservation.